2015
DOI: 10.1038/onc.2015.428
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus core protein interacts with Snail and histone deacetylases to promote the metastasis of hepatocellular carcinoma

Abstract: Downregulation of E-cadherin by the transcriptional repressor Snail is associated with acquisition of metastatic potential. Although hepatitis C virus (HCV) core protein has been implicated in hepatocarcinogenesis, it is unclear whether Snail is involved in HCV core-induced dysregulation of E-cadherin. Herein, we investigated the mechanism by which HCV core induces E-cadherin repression and the role of Snail in HCV core-mediated invasiveness and metastasis. We found that HCV infection, especially HCV core expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 43 publications
2
17
0
Order By: Relevance
“…We found that both Snail and NF-κB were expressed in HCC tissues and that their expression levels were good predictors of the degree of tumor differentiation and of patient survival. Our observation that nearly all HCC patients are positive for both Snail and NF-κB is consistent with earlier studies [8, 13, 1416]. Previous in vitro studies also showed that activation of NF-κB signaling increases Snail expression [6, 12, 13, 17], which is consistent with our finding that levels of Snail expression correlate closely with those of NF-κB expression in human HCC samples.…”
Section: Discussionsupporting
confidence: 93%
“…We found that both Snail and NF-κB were expressed in HCC tissues and that their expression levels were good predictors of the degree of tumor differentiation and of patient survival. Our observation that nearly all HCC patients are positive for both Snail and NF-κB is consistent with earlier studies [8, 13, 1416]. Previous in vitro studies also showed that activation of NF-κB signaling increases Snail expression [6, 12, 13, 17], which is consistent with our finding that levels of Snail expression correlate closely with those of NF-κB expression in human HCC samples.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, a recent study showed that HCV core interacted with Snail and enhanced its binding to the E-cadherin promoter, and HCV core stabilized Snail through the PI3K/Akt/GSK3β pathway, indicating different molecular mechanisms would be involved in the regulation of Snail and EMT in HCV-related HCC. 29 Altogether, these findings provide new insights into the mechanism of HCVmediated invasiveness and metastasis in HCC, and highlight Snail as an attractive molecular target for preventing/treating HCV-related HCC.…”
Section: Discussionmentioning
confidence: 89%
“…The adenoviral recombinant pAd-ARID2 was also generated using the AdEasy system [30]. An analogous adenovirus expressing only GFP (Ad-GFP) and a scrambled shRNA (AdR-siControl) expressing RFP were used as controls.…”
Section: Methodsmentioning
confidence: 99%